Heteronormativity in Criminology: Call for Inclusive Measurement of Sexuality - Gateley, Hannah (Criminal justice review, 2024)
In recent years, scholars’ calls for progress in the field have noted mainstream criminology's historical reluctance to include certain social constructs, particularly sexuality. The current study employed a content analysis to examine articles published between 2015–2019 in Criminology and Journal of Interpersonal Violence (JIV) to determine inclusion of sexuality both within the body of the article and as a variable. Findings indicate while the inclusion of sexuality was limited in both journals, JIV, which has a stated diversity-focused orientation, included sexuality at a higher rate than the mainstream criminological journal, Criminology. Importantly, in both journals, conceptualizations and operationalizations of sexuality, when it was measured as a variable, rarely fell outside of a binary measure. This suggests that the measurement and inclusion of sexuality is still lacking, and the call for inclusivity has not been fully heeded. Unless sexuality is included as a characteristic in research, its impact cannot be definitively determined and, therefore, cannot contribute to the formation of effective policy and practice.